Propuesta de manual de producción audiovisual para el correcto manejo en audio y video para TV Oro Machala. - Valdiviezo Aguilar, Paulo César (2018)
The A/V productions are without excuse main part of all digital world, in the TV journal context, it’s the most trustworthy way of show that the facts had happened, but what happen, when the same facts are so strongest, and attack the integrity of the another people, or even grown up the the genre violence table, On this work, it study the punctual case of TV ORO Machala, his directly competence, his handing A/V products for the journalist notes, the inclusion of the women on his staff, it show us a true example for all city and state.